EL CARIOTIPO FUNDAMENTAL EN RHODOLIRIUM SPECIOSUM(HERB.) RAVENNA Y R. ANDICOLA (POEPP.) RAVENNA (AMARYLLIDACEAE) - Baeza, Carlos M.; Mariangel, Camila; Ruiz, Eduardo; Negritto, María (Gayana Botánica, 2009)
The karyotype of Rhodolirium speciosum (Herb.) Ravenna and R. andicola (Poepp.) Ravenna were examined. The species have 2n = 2x = 16 chromosomes, with 4m + 3sm + 1st chromosomes. Both species present a very different karyotype in comparison to other Amaryllidaceae from Chile.